Companion to sexuality studies - Naples, Nancy A. (Wiley-Blackwell companions to sociology, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres

Genre et psychanalyse : la différence des sexes en question - Rassial, Jean-Jacques; Chevalier, Fanny; Colloque Genre et psychanalyse (Érès poche, 2016)
« La remise en cause de l’évidence naturelle jusque-là accordée à la différence des sexes occupe la scène des débats publics et se retrouve théorisée par l’émergence du concept de « genre » dans sa distinction d’avec le sexe. La différenciation entre sexe et genre émerge d’une fracture avec l’idée que le sexe biologique déterminerait l’identité sexuée et sexuelle. Dans cette nouvelle terminologie, le sexe ne renvoie plus alors qu’à la dimension anatomique et biologique tandis que le genre réfère à la construction psychologique et sociale du sexe. Malgré la pluralité des théories auxquelles le genre a donné naissance, l’émergence de cette notion prend en compte que sexe anatomique, sexuation psychique et sexualité peuvent trouver des nouages autres que ceux promus par des normes confondues avec l’ordre naturel – nouage, souligne la psychanalyse, radicalement singulier pour chacun. Cet ouvrage propose une introduction à toute la complexité de ces questions. Il axe son propos sur les controverses entre les théories psychanalytiques et les études sur le genre, et ouvre le dialogue à la littérature, à la philosophie et au cinéma. Cette perspective pluridisciplinaire reflète ainsi l’hétérogénéité des différents abords et usages du genre. »-- Résumé de l'éditeur.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; cours; discipline; genre; identité sexuelle; identités LGBTQIA2+; post-structuralisme; premier cycle; psy4910; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; sexe/genre; thématiques

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Brain storm: The flaws in the science of sex differences - Jordan-Young, Rebecca M. (Harvard University Press, 2010)
Jordan-Young has written a stunning book that demolishes most of the science associated with the dominant paradigm of the development of sex and gender identity, behavior, and orientation. The current paradigm, brain organization theory, proposes: "Because of early exposure to different sex hormones, males and females have different brains"; and these hormones also create "gay" and "straight" brains. Jordan-Young interviewed virtually every major researcher in the field and reviewed hundreds of published scientific papers. Her conclusion: "Brain organization theory is little more than an elaboration of longstanding folk tales about antagonistic male and female essences and how they connect to antagonistic male and female natures." She explains, in exquisite detail, the flaws in the underlying science, from experimental designs that make no statistical sense to "conceptually sloppy" definitions of male and female sexuality, contradictory results, and the social construction of normality. Her conclusion that the patterns we see are far more complicated than previously believed and due to a wider range of variables will shake up the research community and alter public perception.
Keywords: LGBTQIA2+; analyse critique; approches et analyses; corps; cours; différence des sexes; discipline; discours dominant; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; revue de la littérature; sciences; sciences humaines; sexe/genre; sexisme; sociologie; systèmes d'oppressions; thématiques

Diversité sexuelle et constructions de genre - Chamberland, Line; Frank, Blye W.; Ristock, Janice L. (Collection Santé et societé, 2009)
Les sciences sociales et épidémiologiques contemporaines tendent de plus en plus à prendre en compte la question du genre dans leurs théories sur les orientations sexuelles. Elle mettent ainsi en évidence les diverses articulations entre les formes de sexisme et d'homophobie, et leurs impacts différenciés selon les constructions du genre et les orientations sexuelles, de même qu'en fonction du contexte socioculturel dans lequel elles se situent. Réalisé avec l'appui de l'équipe pancanadienne Sexualités et genres, vulnérabilité et résilience (SVR), cet ouvrage regroupe des contributions de chercheurs francophones et anglophones du Québec, du Canada, de la France et de la Suisse romande, qui examinent les dimensions socioéconomiques, progessionnelles, familiales, relationnelles et psychologiques afin de saisir les variations liées au genre au sein des minorités sexuelles. Faisant appel à des résultats de travaux multidisciplinaires qui s'appuient sur des méthodologies de types quantitatif et qualitatif, ce livre met en lumière des processus contribuant aux inégalités sociales dans les champs de l'éducation, de l'économie et de la santé, et à des condition de vulnérabilité qui affectent l'estime de soi, les réseaux de soutien et la vie sociale. Les recherches observent des modes de résilience significatifs qui, là encore, peuvent varier en fonction du genre, suggérent ainsi sa prise en compte dans les interventions.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; lesbophobie; premier cycle; psy4910; psychologie; rapports sociaux de sexe; ressource en ligne; sciences humaines; sciences sociales; sexe/genre; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; théorie du genre; épistémologie; études de genres

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

Heterosexuals' use of "fag" and "queer" to deride one another: a contributor to heterosexism and stigma - Burn, S M (Journal of homosexuality, 2000)
This paper is on heterosexuals' use of words such as "fag" and "queer" to refer to one another in an insulting manner. This behavior perpetuates heterosexism and the stigmatization of gays. Two hundred and fifty-seven university students (73% Euro-American) served as participants. Males exhibited more anti-gay prejudice and anti-gay behavior than females. Heterosexual males frequently used words such as "fag" and "queer" to put one another down. Anti-homosexual prejudice was predictive of anti-gay behavior. However, approximately half of those who engaged in the behavior were not strongly anti-homosexual. For these individuals, the behavior may win approval from their social group. Awareness campaigns and peer reminders that the derisive use of "fag" and "queer" harms homosexuals may be effective in changing this group. It is more difficult to reduce this behavior in individuals with strong anti-homosexual attitudes. The role of individuals and educational and work organizations in bringing about change is discussed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétérosexisme; insultes; premier cycle; psychologie; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques